Comparative analysis of meat quality and flavor compounds in hot fresh, chilled, and frozen Qingyuan partridge chicken - Hao Qi; Haoming Wang; Zheng Ma; Tianyu Wang; Qinxin He; Haiyi Yu; Xuqing Deng; Zhengfen Zhang; Hui Yu; Hua Li (Applied Food Research)
Flavor is a crucial factor influencing meat quality and consumer acceptance of meat products. This study investigated the differences in meat quality and flavor compounds among three primary forms of commercially available chicken meat: hot fresh, chilled, and frozen. Compared to hot fresh and frozen chicken, chilled chicken exhibited significantly lower cooking loss, muscle fiber cross-sectional area, and muscle fiber diameter in both breast and leg muscles. Chilled chicken also demonstrated higher umami and richness scores. The findings suggested that chilled chicken exhibits more tender meat and enhanced flavor. Volatile flavor compounds (VFCs) analysis revealed that different parts of the chicken can possess distinct flavors. (E,E)-2,4-Decadienal, 1-octen-3-ol, 1-hexanol, 2,3-octanedione, octanal, 2-pentylfuran, hexanal, nonanal, and dodecanal were identified as characteristic volatile compounds in the breast muscle and were determined to be the primary flavor contributors in the chilled fresh breast meat group. 1-Octen-3-ol, 2-nonanone, hexanal, 2-pentylfuran, 1-hexanol, 2,3-octanedione, 2-undecenal, and nonanal were identified as characteristic volatile compounds in the leg muscle, with their contributions varying across storage conditions. Metabolomics analysis demonstrated that chilled chicken had higher levels of flavor precursors such as threonine, taurine, palmitic acid, arachidonic acid, and inosinic acid than that of hot fresh and frozen chicken, respectively. The variations in flavor observed among hot fresh, chilled, and frozen chicken may be attributed to differences in amino acid, sugar, and lipid metabolism. This study elucidates the impact of various post-slaughter storage methods-namely hot fresh, chilled, and frozen-on the quality and flavor characteristics of chicken meat. The findings offer a novel research perspective for optimizing the quality of poultry stored post-slaughter, serve as a reference for future enhancements in chicken flavor, and hold potential applicability in breeding, consumer selection and culinary practices.